Meiotic nucleolar cycle and chromatoid body formation during the rat (Rattus novergicus) and mouse (Mus musculus) spermiogenesis - Peruquetti, Rita Luiza [UNESP]; Assis, Isabella Mariana [UNESP]; Taboga, Sebastiao Roberto [UNESP]; Vilela de Azeredo-Oliveira, Maria Tercilia [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
The aims of the present study were to follow the nucleolar cycle in spermiogenesis of the laboratory rodents Rattus novergicus and Mus musculus, to verify the relationship between the nucleolar component and chromatoid body (CB) formation and to investigate the function of this cytoplasmic supramolecular structure in spermatogenic haploid cells. Histological sections of adult seminiferous tubules were analyzed cytochemically by light microscopy and ultrastructural procedures by transmission electron microscopy. The results reveal that in early spermatids, the CB was visualized in association with the Golgi cisterns indicating that this structure may participate in the acrosome formation process. In late spermatids, the CB was observed near the axonema, a fact suggesting that this structure may support the formation of the spermatozoon tail. In conclusion, our data showed that there is disintegration of spermatid nucleoli at the beginning of spermatogenesis and a fraction of this nucleolar material migrates to the cytoplasm, where a specific structure is formed, known as the "chromatoid body", which, apparently, participates in some parts of the rodent spermiogenesis process. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Nucleolus; Nucleologenesis; Chromatoid body; Spermiogenesis; Cytochemistry; Ultrastructure